1975
DOI: 10.1037/0022-0663.67.5.636
|View full text |Cite
|
Sign up to set email alerts
|

Pictures and young children's learning from oral prose.

Abstract: Wo report, several experiments examining the effects of overt illustration on first graders' learning from oral prose. In all experiments, children hoard prose selections after (or during) which they illustrated selection content with plasticized figure cutouts and background scenes. Control subjects copied or colored geometric forms during the illustration period. After hearing three or five passages, subjects orally recalled passage content and answered simple factual questions about each passage. Illustrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
2

Year Published

1978
1978
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 20 publications
3
51
0
2
Order By: Relevance
“…The positive correlations between drawing accuracy and performance are found when constructed drawings serve as either a memory aid (e.g., Butler et al, 1995) or a study strategy (e.g., Lesgold et al, 1975;Van Meter, 2001). Greene (1989), for example, demonstrated that participants performed better on posttests when drawings accurately depicted text Greene (1989) permitted participants to use the drawn representation at the time of the posttest, these positive correlations are not surprising.…”
Section: The Importance Of Drawing Accuracymentioning
confidence: 99%
See 4 more Smart Citations
“…The positive correlations between drawing accuracy and performance are found when constructed drawings serve as either a memory aid (e.g., Butler et al, 1995) or a study strategy (e.g., Lesgold et al, 1975;Van Meter, 2001). Greene (1989), for example, demonstrated that participants performed better on posttests when drawings accurately depicted text Greene (1989) permitted participants to use the drawn representation at the time of the posttest, these positive correlations are not surprising.…”
Section: The Importance Of Drawing Accuracymentioning
confidence: 99%
“…The empirical literature is clear, however. Lesgold et al (1975Lesgold et al ( , 1977 and Van Meter (2001) demonstrate the importance of drawing accuracy when designing classroom implementations that use drawing as a comprehension or learning strategy.…”
Section: The Importance Of Drawing Accuracymentioning
confidence: 99%
See 3 more Smart Citations